Perbandingan Efektifitas Antara Penggunaan Bupivacaine Hiperbarik Dengan Levobupivacaine Isobarik Pada Pasien Sectio Caesaria Dengan Anestesi Spinal - Tri Budi Santoso; Cemy Nur Fitria; Fatoni Hutagalung (Jurnal Ventilator, 2023)
Background: Regional anesthesia is a major factor in safety patients during labor by Sectio Caesaria (SC). The rise of spinal anesthesia as a popular technique in use made possible by the development of a small needle with a tip pencil and has become the anesthetic method of choice for elective surgery and for multiple emergency cesarean deliveries if an epidural catheter not there yet. Research method: This research is an experimental analytic observational study with a cross sectional study approach. Result: Known Asymp value. Sig. (2-tailed) of 0.734 because the value of asymp. Sig (2-tailed) > 0.05 or 0.0734 > 0.05, it can be concluded that H0 is accepted, Ha is rejected, so no. Comparison between the use of hyperbaric bupivacaine and isobaric levobupivacaine in cesarean section patients with spinal anesthesia. Conclusion: There is no comparison between the use of hyperbaric bupivacaine and isobaric levobupivacaine in cesarean section patients with spinal anesthesia.